Hiring in border regions: Experimental and qualitative evidence from a recruiter survey in Luxembourg - Tamara Gutfleisch; Robin Samuel (Journal for Labour Market Research, 2022)
Firms in border regions typically deal with heterogeneous applicant pools that include both (foreign) domestic workers and cross-border commuters. However, we know little about recruiters' workforce needs and hiring practices in cross-border labour markets. Based on a survey of real recruiters in Luxembourg, this study presents experimental and qualitative findings on the role of country of residence in recruiters' hiring intentions against foreigners. Luxembourg presents a rarely studied but highly relevant case for hiring practices owing to a combination of a strong economy, strict labour market regulations, and a transnational workforce. Drawing on data from a factorial survey experiment, we found no discrimination against Portuguese and French applicants living in Luxembourg. Yet, (highly skilled) cross-border workers from France and Germany faced disadvantages regarding recruiters' hiring intentions. However, differences in effect sizes between foreigners and cross-border workers were small and not statistically significant. When further asked about the potential challenges of recruiting in Luxembourg's cross-border labour market, respondents expressed concerns about flexibility, poor social fit, and cultural differences in hiring foreign and cross-border employees. Overall, our study provides further points of reference for studies on hiring intentions in cross-border labour markets across Europe.
Keywords: M51; J71; J61; R23; 330; Hiring intentions; Cross-border labour mobility; International workforce; Factorial survey experiment; Luxembourg